Ocorrência e identificação de coccídeos em amostras fecais de passeriformes silvestres (Aves: Passeriformes) no Centro de Triagem de Animais Silvestres do IBAMA em Belo Horizonte - Cecilia Barreto (2014)
This study aimed to assess the occurrence of oocysts in feces of native Brazilian passerines (Aves: Passeriformes) in a triage center for wild animals (IBAMA, Belo Horizonte, Brazil) during the period from August 21 to September 21, 2012. The risk attributed to the host Family and species, and the characterization and identification of species of coccidia were determined. Two hundred and sixteen (n=216) fecal samples of individuals of families Cardinalidae, Emberizidae, Fringillidae, Icteridae, Thraupidae and Turdidae were evaluated. Oocyst positive samples were found in 28,24% of feces of families Emberizidae, Thraupidae, Cardinalidae and Icteridae, and all (100%) were characterized as Isospora. The assessment of risk attributable to family indicated Thraupidae as the most likely host to be positive, with a greater probability of presenting oocysts than Cardinalidae, Emberizidae, Fringilidae and Turdidae. Analysis of Icteridae suggests a greater probability of oocysts than Cardinalidae. The evaluation of risk according to host species within Thraupidae indicated a risk 66.9 % greater for Saltator similis than Lanio pileatus, and 27.9 % greater for Sporophila caerulescens than Sporophila nigricolis, for presenting fecal oocysts. Results demonstrated for the first time Isospora in feces of Cyanoloxia brisonii, Gnorimopsar chopi, Paroaria dominicana, Schistochlamys ruficapillus and Sporophila nigricolis. New species were named as I. gnorimopsar and I. chopi in G. chopi, I. dominicana, in P. dominicana, I. beagai and I. ferri, in S. similis, I. ruficapillus in S. ruficapillus and I. nigricolis in S. nigricolis.